ANALISIS PENERAPAN SAK EMKM DALAM PENYUSUNAN LAPORAN KEUANGAN UMKM: (Studi Kasus pada UMKM Rejeki Mekar Abadi Purworejo) - Karimah (Transpublika Publisher, 2023)
This study aims to find out how the financial reporting process of the Rejeki Mekar Abadi company, as well as the problems faced by the Rejeki Mekar Abadi company in preparing financial statements, and the company's understanding of the presentation of financial statements in accordance with SAK-EMKM or Financial Accounting Standards for Micro, Small and Medium Entities. This qualitative study was conducted with a descriptive design. Data for this study were collected through observations, interviews, and document analysis. The results showed that Rejeki Mekar Abadi includes as MSME business but has not fully implemented SAK-EMKM standard. Financial statements are prepared based on individual skills, and the company's financial statements cannot be used as a consideration in making company decisions.